2021
DOI: 10.1101/2021.05.25.21257730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-COVID assessment in a specialist clinical service: a 12-month, single-centre analysis of symptoms and healthcare needs in 1325 individuals

Abstract: Background. Complications following SARS-CoV-2 infection require simultaneous characterisation and management to plan policy and health system responses. We describe the 12-month experience of the first UK dedicated Post-COVID clinical service to include both hospitalised and non-hospitalised patients. Methods. In a single-centre, observational analysis, we report outcomes for 1325 individuals assessed in the University College London Hospitals NHS Foundation Trust Post-COVID service between April 2020 and Ap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“… 7 Reported fatigue has ranged markedly in the studies to date, with a higher proportion fatigued in the non-hospitalised population than those hospitalised. 3 Mandal et al 8 noted fatigue in 69% of patients at 378 days, and Huang et al 9 identified 63% with self-reported fatigue or muscle weakness at 153 days post-discharge; however, our data, in a non-hospitalised population, is lower than this. In a non-hospitalised population, Petersen et al 10 reported a similar incidence to the current study (<30%) 4 months following acute illness.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“… 7 Reported fatigue has ranged markedly in the studies to date, with a higher proportion fatigued in the non-hospitalised population than those hospitalised. 3 Mandal et al 8 noted fatigue in 69% of patients at 378 days, and Huang et al 9 identified 63% with self-reported fatigue or muscle weakness at 153 days post-discharge; however, our data, in a non-hospitalised population, is lower than this. In a non-hospitalised population, Petersen et al 10 reported a similar incidence to the current study (<30%) 4 months following acute illness.…”
Section: Discussioncontrasting
confidence: 72%
“…This demonstrates a wider physical and psychosocial impact beyond the acute illness phase. 1 Recent studies of hospitalised and non-hospitalised cohorts 1,3 identified a number of symptoms and post-COVID phenotypes spanning mental and physical health.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 2184 citations, screened 1806 titles and abstract, 65 full text and included 12 articles reporting on care models for Long COVID (Figure 1) [10][11][12][13][14][15][16][17][18][19][20][21] .…”
Section: Literature Searchmentioning
confidence: 99%
“…Up to a third of people may have symptoms for 12 months or more (Whitaker et al, 2021). Two Long Covid clinics have identified difference between hospitalised and non-hospitalised patients (Heightman et al, 2021;O'Sullivan et al, 2021). Long Covid includes people who have been critically ill (including children with paediatric multi-system inflammatory syndrome) and are experiencing post-intensive care syndrome, some with clear organ damage from the initial viral attack.…”
Section: Beyond the Acute Phase Of Covid-19 Infectionmentioning
confidence: 99%